ANALISIS PERTUNJUKKAN KENTRUNG KI DALANG H. KHUSAIRI CERITA SUNAN DRAJAAT (KAJIAN STRUKTUR, MAKNA, FUNGSI, DAN RESEPSI) - Agustina, Feny Rizki Eka; Mustofa, Mustofa; Selirowangi, Nisaul Barokati (Fakultas Keguruan dan Ilmu Pendidikan Unisda Lamongan, 2024)
This study aims to describe the structure, meaning, function and reception of the community that is present at the exhibition of the Sunan Drajat. This research was conducted using qualitative descriptive methods. Qualitative descriptive method is a method that produces data in the form of writing and oral in a language community based on facts and information and informants. The method of obtaining data is done by using observation techniques. The researcher directly observes the continuity of the Sunan Drajat performance. The use of observation techniques is also supported by interview techniques, and library data. In analyzing the data, the steps are based on structure, meaning, function, and reception. Data relating to the structure are analyzed using the theory of performance structures and literary structures. Data relating to meaning is analyzed using a verbal and non verbal semantic approach. Data relating to functions is analyzed using literary function theory. Data relating to community receptions are analyzed using theories and responses. The results of this study are in the form of structure, meaning, function and public reception. From the results of the close analysis Sunan Drajat, has several structures, namely there is a structure of performance and literary structure, the structure of the performance includes the stage, fashion or costume, makeup while the literary structure includes the plot, character and characterization, setting, point of view, morality or mandate. Kentrung Sunan Drajat in literature has verbal and non verbal meanings, verbal meanings include (1) flying and jedor, (2) gong and puppets, (3) pangkur songs while non-verbal meanings include (1) suluk, (2) Sunan Drajat tomb , (3) Singo Mengkok gamelan. From the analysis of the function of the kentrung story Sunan Drajat there are functions such as: (1) as an educational tool, (2) as a means of public entertainment, (3) as a means of preaching Islam, (4) as a means of social criticism, (5) as a means of developing self existence. From the analysis of the kentrung story show Sunan Drajat there is a public reception by producing some criticisms and responses from people who have interests and audience.